2011
DOI: 10.1021/ol103069d
|View full text |Cite
|
Sign up to set email alerts
|

Highly Enantioselective Synthesis of Polysubstituted Tetrahydroquinolines via Organocatalytic Michael/Aza-Henry Tandem Reactions

Abstract: Highly enantioselective chiral bifunctional thiourea catalyzed asymmetric tandem reactions for synthesis of substituted tetrahydroquinolines are described. Substituted tetrahydroquinolines were given in good yields (up to 98%), high enantioselectivities (up to >99% ee), and diastereoselectivities (up to 20:1 dr).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(26 citation statements)
references
References 53 publications
0
26
0
Order By: Relevance
“…Recently, we communicated a new method for the two‐component, two‐step synthesis of polysubstituted tetrahydroquinoline derivatives through an organocatalytic asymmetric tandem Michael addition and aza‐Henry reaction [Eq. (1)] 7. This type of reaction yields the cis ‐isomer at the 2,3‐positions.…”
Section: Screening Of the Reaction Conditions[a]mentioning
confidence: 96%
“…Recently, we communicated a new method for the two‐component, two‐step synthesis of polysubstituted tetrahydroquinoline derivatives through an organocatalytic asymmetric tandem Michael addition and aza‐Henry reaction [Eq. (1)] 7. This type of reaction yields the cis ‐isomer at the 2,3‐positions.…”
Section: Screening Of the Reaction Conditions[a]mentioning
confidence: 96%
“…In all cases the reactions smoothly proceeded under very mild conditions, and the desired functionalized products (6)(7)(8)(9)(10)(11)(12)(13)(14) were obtained in good yield and diastereoselectivity and excellent enantioselectivity (up to 99% ee).…”
Section: Resultsmentioning
confidence: 93%
“…In more detail, we planned a new two-component cascade, in which nitromethane acted as a double-donor towards two differently reactive acceptors present in the same molecule. [12] Only Xu and co-workers [13] reported a similar tandem double addition of nitromethane, but they employed an imine and an a,b-unsaturated ketone as acceptors, thus carrying out a Michael/Henry sequence [Scheme 1, Eq. [12] Only Xu and co-workers [13] reported a similar tandem double addition of nitromethane, but they employed an imine and an a,b-unsaturated ketone as acceptors, thus carrying out a Michael/Henry sequence [Scheme 1, Eq.…”
Section: Introductionmentioning
confidence: 99%
“…[95] The authors have shown that installing an electron-withdrawing sulfone group on the amino group of 2-aminobenzaldehydes allowed for their activation, since the corresponding sulfonated 3-nitro-1,2-dihydroquinolines were generally obtained in better yields (75-92%), and enantioselectivities (70-90% ee). More recently, Xu et al developed an access to 2,3,4-trisubstituted tetrahydroquinolines 188a-g on the basis of asymmetric domino Michaelaza-Henry reactions involving nitromethane and chalcones 189a-g. [96] When these reactions were catalyzed with bifunctional thiourea 190, they furnished the potential biologically active polysubstituted tetrahydroquinolines 188a-g in generally both excellent yields (94-98%) and enantioselectivities (98 to > 99% ee) combined with moderate to high diastereoselectivities of up to 90% de, as shown in Scheme 51.…”
Section: Domino Michael-(aza)-henry Reactionsmentioning
confidence: 99%